Doxycycline Suppresses Vasculogenic Mimicry in Human Pterygium Fibroblasts. (3rd October 2022) - He, Meng-Xuan; Zhang, Jun-Fang; Yang, Ling; Qin, Bai; Gu, Hong-Wei; Tang, Qiu-Yang; Guan, Huai-Jin; Shi, Hai-Hong
Abstract: Purpose: To explore the effect of doxycycline on vasculogenic mimicry (VM) formation and the potential mechanism in human pterygium fibroblasts in order to find novel targets for pterygium therapy. Methods: First, we demonstrate the existence of VM in 73 pterygium specimens by CD31 and periodic acid Schiff (PAS) dual staining. Then we used cell counting kit-8, clone formation assay and flow cytometry to prove the inhibitory effect of doxycycline on cell proliferation and apoptosis. The VM formation was evaluated through wound healing assay, cell transwell assay and three-dimensional cell culture combined with PAS staining. Finally, we used Western blot to testify the correlation of the VM and the factors in protein level preliminarily. Results: Our results showed that VM existed in human pterygium specimens exactly. Otherwise, in human pterygium fibroblasts, doxycycline induced a dose-dependent inhibitory effect on cell proliferation and apoptosis induction. Besides, doxycycline significantly suppressed vasculogenic mimicry tube formation, cell migration and invasion. Furthermore, doxycycline impaired the expression of MMP-9, MMP-2 and VEGF which may related to pterygium VM formation. Conclusions: Doxycycline decelerated pterygium progression might be through inhibiting VM formation according to the downregulation of MMP-9, MMP-2 and VEGF, which may provide the basis of further studies involving doxycycline for pterygium treatment.